Review of the status of learning in research on Sport Education: Future research and practice - Araújo, Rui; Mesquita, Isabel; Hastie, Peter A (Journal of sports science & medicine, 2014)
Research concerning Sport Education's educational impact has shown unequivocal results according to students' personal and social development. Nevertheless, research is still sparse with respect to the model's impact on student learning outcomes. The goal of the present review is to therefore scrutinize what is currently known regarding students' learning during their participation in Sport Education. This research spans a variety of studies, cross various countries, school grades, the sports studied, as well as the methods applied and dimensions of student learning analyzed. While research on the impact of Sport Education on students' learning, as well as teachers' and students' perceptions about student learning has shown students' improvements during the participation in Sport Education seasons, there is still considerable variance in these results. For example, some studies report superior learning opportunities to boys and higher skill-level students while other studies have identified superior learning opportunities for girls and lower skill-level students. These inconsistent results can be explained by factors not considered in the Sport Education research, such as the effect of time on students' learning and the control of the teaching-learning process within Sport Education units. In this review directions for future research and practice are also described. Future research should define, implement, and evaluate protocols for student-coaches' preparation in order to understand the influence of this issue on students' learning as well as consider the implementation of hybrid approaches. Moreover, future studies should consider the interaction of gender and skill level and a retention test in the analysis of students' learning improvements in order to obtain a more realist and complete portrait of the impact of Sport Education. Finally, in order to reach an entirely understanding of the teaching-learning process, it is necessary to use research designs that attend to the complexity of this process. Verf.-Referat.